2013
DOI: 10.7182/pit2013788
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Single Item to Assess Daytime Sleepiness for the Swiss Transplant Cohort Study

Abstract: The accumulated evidence provided evidence for the validity of the STCS daytime sleepiness item as a simple screening scale for daytime sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Given that some studies have shown poor correlation of sleepiness assessed with different measurement tools and poor agreement between subjective and objective measures of sleepiness [33], the use of a single question to measure daytime sleepiness could have led to measurement error that could have tempered a potential association. However, single-item measures of sleepiness have also been shown to serve as effective screening tools [34,35]. Third, we had limited power to observe significant associations due to low case counts, particularly for stroke, which had only 18 cases for women who reported experiencing daytime sleepiness almost every day.…”
Section: Discussionmentioning
confidence: 98%
“…Given that some studies have shown poor correlation of sleepiness assessed with different measurement tools and poor agreement between subjective and objective measures of sleepiness [33], the use of a single question to measure daytime sleepiness could have led to measurement error that could have tempered a potential association. However, single-item measures of sleepiness have also been shown to serve as effective screening tools [34,35]. Third, we had limited power to observe significant associations due to low case counts, particularly for stroke, which had only 18 cases for women who reported experiencing daytime sleepiness almost every day.…”
Section: Discussionmentioning
confidence: 98%
“…The stage sampling approach used was based on candidates’ PSQI and ESS scores, both of which were assessed as a part of the larger study [8]. The PSQI is a self-rated questionnaire consisting of 19 items, assessing a wide variety of factors related to sleep quality over a 1 month period, including estimates of sleep duration and latency, and of the frequency and severity of specific sleep-related problems.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were informed at the start of the research project [8] that they might be invited for a further screening and assessment if their initial data indicated poor SQ and/or DS (see flowchart, Figure 1). Each such patient received a package containing an information letter, informed consent documents, a pre-stamped return envelope and the Survey of Sleep questionnaire (SOS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations